2019
DOI: 10.1002/sctm.19-0173
|View full text |Cite
|
Sign up to set email alerts
|

Adult tissue–derived neural crest-like stem cells: Sources, regulatory networks, and translational potential

Abstract: Neural crest (NC) cells are a multipotent stem cell population that give rise to a diverse array of cell types in the body, including peripheral neurons, Schwann cells (SC), craniofacial cartilage and bone, smooth muscle cells, and melanocytes. NC formation and differentiation into specific lineages takes place in response to a set of highly regulated signaling and transcriptional events within the neural plate border. Premigratory NC cells initially are contained within the dorsal neural tube from which they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 179 publications
(299 reference statements)
0
41
0
Order By: Relevance
“…216,217 Although lineage tracing studies using P0 and/or Wnt1-cre recombination in mice have identified the NC origin of some of these neonatal and adult stem cell populations and/or the expression of common NC markers, 10,201,205,209,210 the mechanisms that maintain their stemness and the physiological roles of these cells are poorly understood. The NC-derived stem cells isolated from neonatal or adult tissues maintain high stem cell potency and can be differentiated into several of the NC derivatives such as neurons, glia, smooth muscle cells, melanocytes, bone cells, fibroblasts, and chondrocytes in vitro (reviewed in detail elsewhere 218,219 The discovery of NC-derived stem cells in skin has been particularly exciting considering this could be an easily accessible source of the cells for autologous transplantation for treatment of disease conditions. Since this discovery, several studies have isolated NC-derived progenitor or stem cells from human skin.…”
Section: Nc-derived Stem Cell Reservoirs In Neonatal and Adult Tissuesmentioning
confidence: 99%
“…216,217 Although lineage tracing studies using P0 and/or Wnt1-cre recombination in mice have identified the NC origin of some of these neonatal and adult stem cell populations and/or the expression of common NC markers, 10,201,205,209,210 the mechanisms that maintain their stemness and the physiological roles of these cells are poorly understood. The NC-derived stem cells isolated from neonatal or adult tissues maintain high stem cell potency and can be differentiated into several of the NC derivatives such as neurons, glia, smooth muscle cells, melanocytes, bone cells, fibroblasts, and chondrocytes in vitro (reviewed in detail elsewhere 218,219 The discovery of NC-derived stem cells in skin has been particularly exciting considering this could be an easily accessible source of the cells for autologous transplantation for treatment of disease conditions. Since this discovery, several studies have isolated NC-derived progenitor or stem cells from human skin.…”
Section: Nc-derived Stem Cell Reservoirs In Neonatal and Adult Tissuesmentioning
confidence: 99%
“…Within dental tissues, there are five main classes of MSC populations, including (I) dental pulp stem cells (DPSCs), (II) stem cells from exfoliated deciduous teeth (SHEDs), (III) periodontal ligament stem cells (PDLSCs), (IV) dental follicle progenitor stem cells (DFPSCs), and (V) stem cells from apical papilla (SCAPs) [ 26 ]. Beyond the five main classes, neural crest stem cells have also emerged as a prominent cell population arising in the dorsal neural tube that give rise to a diverse array of cell types in the body, including craniofacial cartilage and bone [ 27 ]. The most easily extracted and isolated of the aforementioned odontogenic cell lines are the SHEDs, commonly isolated through minimally invasive approaches.…”
Section: Stem Cells In Palatal Bone Regenerationmentioning
confidence: 99%
“…So far non-myelinating and myelinating Schwann cells participate to CNS repair. Stem cells are also present in the adult PNS and namely in the adult DRG (reviewed in (Mehrotra, Tseropoulos, Bronner, & Andreadis, 2019)). Yet their activation and involvement in response to CNS injury remains to be addressed.…”
Section: Conclusion /Perspectivesmentioning
confidence: 99%